Blunt force trauma in the Canarian houbara bustard (Chlamyd-otis undulata fuertaventurae) produced by collision with overhead lines - C.M. Suárez-Santana; L. Marrero-Ponce; J. Navarro-Sarmiento; C. Rivero Herrera; R. Grandía Guzmán; A. Colom-Rivero; Ó. Quesada-Canales; E. Sierra; A. Fernández (Journal of Comparative Pathology, 2025)

Detection of highly pathogenic avian influenza H5N1 in marine mammals from South America - E. Sierra; M. Ulloa; C. Fiorito; A. Colom-Rivero; V. Neira; A. Fernández (Journal of Comparative Pathology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Factors shaping the abundance of two butterflies sharing resources and enemies across a biogeographic region - P. Colom; A. Traveset; M. R. Shaw; C. Stefanescu (Journal of Biogeography, 2024)
Aim Intraspecific variation in species relative abundance is shaped by a complex interplay of abiotic and biotic factors, making it both necessary and challenging to assess their combined relative importance in explaining variations across space and time. We used two congeneric butterfly species for which extensive count data and a deep understanding of their natural history is available to test three hypotheses explaining intraspecific variation in their abundance: (H1) seasonal dispersal behaviour driven by climate, (H2) resource availability and (H3) apparent competition mediated via shared parasitoids. Taxon Gonepteryx rhamni (Brimstone) and G. cleopatra (Cleopatra). Location NE Iberian Peninsula, where both species coexist, and a nearby archipelago (Balearic Islands), where only Cleopatra occurs. Methods We analysed spatial abundance variations for both species in the mainland and island–mainland differences in the abundance of Cleopatra. Abiotic and biotic factors, including temperature, host plant and overwintering habitat availability, larval parasitism and density dependence, were tested to explain the observed variations. Results H1 can explain variation in butterfly abundance between mainland regions since in warmer summers populations increased in cooler areas but decreased in warmer areas. H2 explains the variation within mainland climate regions with a strong positive relationship between resource availability and abundance but is unlikely to explain the island–mainland variation in the abundance of Cleopatra. H3 could neither explain biogeographical variation in abundance because although richer parasitoid communities were found on the mainland, larval mortality rates were similar or lower on the mainland than in the islands. Main Conclusions Climate and resource availability jointly account for variation in butterfly abundance across the mainland, but neither these factors nor parasitism can explain island–mainland differences. Both coexisting butterfly species and their larval parasitoids may have undergone evolutionary processes, resulting in spatial segregation that promotes the coexistence of the two butterfly species on the mainland.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

The CO 2 ‐equivalent balance of freshwater ecosystems is non‐linearly related to productivity - Charlotte Grasset; Sebastian Sobek; Kristin Scharnweber; Simone Moras; Holger Villwock; Sara Andersson; Carolin Hiller; Anna C. Nydahl; Fernando Chaguaceda; William Colom; Lars J. Tranvik (Global Change Biology, 2020)
Eutrophication of fresh waters results in increased CO 2 uptake by primary production, but at the same time increased emissions of CH 4 to the atmosphere. Given the contrasting effects of CO 2 uptake and CH 4 release, the net effect of eutrophication on the CO 2 ‐equivalent balance of fresh waters is not clear. We measured carbon fluxes (CO 2 and CH 4 diffusion, CH 4 ebullition) and CH 4 oxidation in 20 freshwater mesocosms with 10 different nutrient concentrations (total phosphorus range: mesotrophic 39 µg/L until hypereutrophic 939 µg/L) and planktivorous fish in half of them. We found that the CO 2 ‐equivalent balance had a U‐shaped relationship with productivity, up to a threshold in hypereutrophic systems. CO 2 ‐equivalent sinks were confined to a narrow range of net ecosystem production (NEP) between 5 and 19 mmol O 2 m −3 day −1 . Our findings indicate that eutrophication can shift fresh waters from sources to sinks of CO 2 ‐equivalents due to enhanced CO 2 uptake, but continued eutrophication enhances CH 4 emission and transforms freshwater ecosystems to net sources of CO 2 ‐equivalents to the atmosphere. Nutrient enrichment but also planktivorous fish presence increased productivity, thereby regulating the resulting CO 2 ‐equivalent balance. Increasing planktivorous fish abundance, often concomitant with eutrophication, will consequently likely affect the CO 2 ‐equivalent balance of fresh waters.

Fundamental niche prediction of the pathogenic yeasts Cryptococcus neoformans and Cryptococcus gattii in Europe - Massimo Cogliati; Erika Puccianti; Maria T. Montagna; Antonella De Donno; Serdar Susever; Cagri Ergin; Aristea Velegraki; Mohamed S. Ellabib; Simona Nardoni; Cristina Macci; Laura Trovato; Ludovico Dipineto; et al. (Environmental Microbiology, 2017)
Summary Fundamental niche prediction of Cryptococcus neoformans and Cryptococcus gattii in Europe is an important tool to understand where these pathogenic yeasts have a high probability to survive in the environment and therefore to identify the areas with high risk of infection. In this study, occurrence data for C . neoformans and C . gattii were compared by MaxEnt software with several bioclimatic conditions as well as with soil characteristics and land use. The results showed that C . gattii distribution can be predicted with high probability along the Mediterranean coast. The analysis of variables showed that its distribution is limited by low temperatures during the coldest season, and by heavy precipitations in the driest season. C . neoformans var. grubii is able to colonize the same areas of C . gattii but is more tolerant to cold winter temperatures and summer precipitations. In contrast, the C . neoformans var. neoformans map was completely different. The best conditions for its survival were displayed in sub‐continental areas and not along the Mediterranean coasts. In conclusion, we produced for the first time detailed prediction maps of the species and varieties of the C . neoformans and C . gattii species complex in Europe and Mediterranean area.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Gray matter responsiveness to adaptive working memory training: a surface-based morphometry study - Francisco J. Román; Lindsay B. Lewis; Chi-Hua Chen; Sherif Karama; Miguel Burgaleta; Kenia Martínez; Claude Lepage; Susanne M. Jaeggi; Alan C. Evans; William S. Kremen; Roberto Colom (Brain Structure and Function, 2016)

Sphinganine and sphingosine levels and ratio in urine and blood samples from a Catalonian population, Spain - G. Cano-Sancho; S. Marin; V. Sanchis; C. Colom; M.B. Coronel; A.J. Ramos (Food Additives & Contaminants: Part A, 2011)

Native fructose extracted from apple improves glucose tolerance in mice - C. Dray; A. Colom; C. Guigné; S. Legonidec; A. Guibert; F. Ouarne; P. Valet (Journal of Physiology and Biochemistry, 2009)